Social Innovation for Work Inclusion – Contributions of Swedish Third Sector Organizations - Lindberg, Malin; Hvenmark, Johan; Nahnfeldt, Cecilia (Nordic Journal of Working Life Studies, 2022)
The innovative contributions of third sector organizations (TSOs) to tackle work-related societal challenges are increasingly acknowledged in policy and research, but rarely in Nordic working life studies. The article helps fill this knowledge gap by an empirical mapping of efforts by Swedish TSOs to promote work inclusion among people considered disadvantaged in the regular labor market, due to age, disabilities, origin, etc. Previous studies of social innovation help distinguish their innovativeness in terms of alternative or complementary ways to perceive and promote work inclusion in regard to Swedish labor market policies. By combining various measures for providing and preparing work opportunities, addressing their participants through individualistic and holistic approaches, and managing work inclusion by varying organization, funding, and alliances, the mapped cases seem to innovatively compensate for government and market failures in the work inclusion domain to some extent, while also being limited by their own voluntary failures.